Impact of Greenland orography on the Atlantic Meridional Overturning Circulation - Davini, P.; von Hardenberg, J.; Filippi, L.; Provenzale, A. (Geophysical Research Letters, 2015)
We show that the absence of the Greenland ice sheet would have important consequences on the North Atlantic Ocean circulation, even without taking into account the effect of the freshwater input to the ocean from ice melting. These effects are investigated in a 600year long coupled ocean-atmosphere simulation with the high-resolution global climate model EC-Earth 3.0.1. Once a new equilibrium is established, a cooling of Eurasia and of the North Atlantic and a poleward shift of the subtropical jet are observed. These hemispheric changes are ascribed to a weakening of the Atlantic Meridional Overturning Circulation (AMOC) by about 12%. We attribute this slowdown to a reduction in salinity of the Arctic basin and to the related change of the mass and salt transport through the Fram Straita consequence of the new surface wind pattern over the lower orography. This idealized experiment illustrates the sensitivity of the AMOC to local surface winds.